Influenza A Virus Pre-Infection Exacerbates Pseudomonas aeruginosa-Mediated Lung Damage Through Increased MMP-9 Expression, Decreased Elafin Production and Tissue Resilience - Villeret, Berengère; Solhonne, Brigitte; Straube, Marjolène; Lemaire, Flora; Cazes, Aurélie; Garcia-Verdugo, Ignacio; Sallenave, Jean-Michel (Frontiers in Immunology, 2020)
Individuals with impaired immune responses, such as ventilated and cystic fibrosis patients are often infected with Pseudomonas aeruginosa (P.a) bacteria, and co-infection with Influenza virus (IAV) is often present. It has been known for many years that infection with IAV predisposes the host to secondary bacterial infections (such as S.pneumoniae or S.aureus), and mechanistic studies abound, including those studying the role of desentization of TLR signalling, type I IFN- mediated impairment of neutrophil chemokines and antimicrobial production, attenuation of IL1 production etc... To study the potential deleterious synergy between Influenza and P.a co-infections, often observed in lung diseases, including cystic fibrosis. We demonstrate here in vitro in epithelial cells and in vivo in three independent models (two involving mice given IAV +/- P.a, and one involving mice given IAV +/- IL-1) that IAV promoted secondary P.a-mediated lung disease or augmented IL-1-mediated inflammation. We showed that IAV-P.a-mediated maladaptive responses included increased matrix metalloprotease (MMP) activity, and MMP-9 in particular, which could be rescued in vivo by the use of the MMP inhibitor batimastat. Furthermore, we showed that IAV post-transcriptionally targeted the antimicrobial/anti-protease molecule elafin/trappin-2, which we have shown previously to be anti-inflammatory and to protect the host against maladaptative neutrophilic inflammation in P.a infections. Our work highlights the capacity of IAV to promote further P.a-mediated lung damage, not necessarily through its interference with host resistance to the bacterium, but instead through down-regulating tissue resilience to lung inflammation. Our study therefore suggests that restoring tissue resilience in clinical settings where IAV/P.a co-exist could be a fruitful strategy.